1990
DOI: 10.1055/s-2008-1046174
|View full text |Cite
|
Sign up to set email alerts
|

Résultats préliminaires de la technique d'excision du ptérygion avec autogreffe conjonctivale

Abstract: 14 eyes with a pterygium, including one eye from which a pterygium had previously been removed by a simple excision, underwent a conjunctival autograft. During an average follow-up of 13 months, we observed a recurrence in 5 eyes (35%). The visual acuity stayed unchanged in 10 eyes, worsened in 1 eye and improved in 3 eyes. The corneal astigmatism measured with a Javal keratometer showed a modification in 12 eyes. This method should not be used as a standard primary surgery for pterygium in view of the high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…7,8 With conjunctival autograft transplantation (CAT), these rates drop to 2%-35%. 9 Using antimetabolites with surgery is the most widely used treatment alternative. Although low recurrence rates are observed with [10][11][12] or without 13 a defined surgical technique, mitomycin C, the most frequently used antimetabolite in pterygium treatment, has limited value owing to its potentially toxic effects.…”
mentioning
confidence: 99%
“…7,8 With conjunctival autograft transplantation (CAT), these rates drop to 2%-35%. 9 Using antimetabolites with surgery is the most widely used treatment alternative. Although low recurrence rates are observed with [10][11][12] or without 13 a defined surgical technique, mitomycin C, the most frequently used antimetabolite in pterygium treatment, has limited value owing to its potentially toxic effects.…”
mentioning
confidence: 99%
“…It was reported that increasing age was associated with fewer recurrences in patients who underwent conjunctival autograft (7). On the other hand, the mean ages of patients with recurrence in the studies by Lewallen, Simona et al, and Dadeya et al were 29, 38, and 27 years, respectively (8,39,46). Guler et al reported that all recurrences occurred in patients who underwent limbal conjunctival autografting who were below the age of 40 years (45).…”
Section: Discussionmentioning
confidence: 99%
“…Since presence of Tenon's capsule in the graft may cause transient postoperative graft edema or retraction of the graft, attention should be paid to dissect this capsule from both the donor conjunctiva and the receptor bed (39,46). We injected an adequate amount of saline into the space between conjunctiva and Tenon's capsule.…”
Section: Discussionmentioning
confidence: 99%